2006
DOI: 10.1287/isre.1060.0083
|View full text |Cite
|
Sign up to set email alerts
|

Research Note—Information Technology, Contract Completeness, and Buyer-Supplier Relationships

Abstract: The theory of incomplete contracts has been used to study the relationship between buyers and suppliers following the deployment of modern information technology to facilitate coordination between them. Previous research has sought to explain anecdotal evidence from some industries on the recent reduction in the number of suppliers selected to do business with buyers, by appealing to relationship-specific costs that suppliers may incur. In contrast, this paper emphasizes the fact that information technology en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 19 publications
2
31
0
Order By: Relevance
“…As previous research has shown, EDI adoption requires asset specific investments by suppliers (Bakos and Brynjolfsson 1993;Howells and Wood 1995;Banker et al 2000;Subramani and Walden 2000;Grewal 2001). The large asset specificity, however, is not a major concern for potential participants in EM as it is in EDI because advances in the Internet technology have dramatically decreased the cost of implementing and maintaining an EM (Clemons et al 1993).…”
Section: Edi Adoptionmentioning
confidence: 94%
See 1 more Smart Citation
“…As previous research has shown, EDI adoption requires asset specific investments by suppliers (Bakos and Brynjolfsson 1993;Howells and Wood 1995;Banker et al 2000;Subramani and Walden 2000;Grewal 2001). The large asset specificity, however, is not a major concern for potential participants in EM as it is in EDI because advances in the Internet technology have dramatically decreased the cost of implementing and maintaining an EM (Clemons et al 1993).…”
Section: Edi Adoptionmentioning
confidence: 94%
“…To analyze factors, which influence the supplier's adoption of PEM, incomplete contract theory and social exchange theory, which have been adopted to analyze the buyer-supplier relationship, are utilized in this study (Bakos and Brynjolfsson 1993;Young-Ybarra and Wiersema 1999;Banker et al 2000;Subramani and Walden 2000).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Consistent with the strategy literature (Banker et al 2006;Bierly & Chakrsbarti 1996;Teece 2007), we define social media strategic capability as the ability to acquire, integrate, and apply knowledge from social media to organizational resources in alignment with an organization's strategic directions and choices, thus enabling the capabilities to be swift and flexible. On social media, rapid and flexible decision making are vital in allowing firms to commit resources and behaviors to new innovations (e.g.,…”
Section: Direct Effect Of Social Media Strategic Capability On Brand mentioning
confidence: 99%
“…A distinctive characteristic of a successful firm is its ability to be flexible in its strategic directions by responding to rapid environmental changes that include widespread market information, technological uncertainties, and competitor activities (Banker, Kalvenes, & Patterson 2006;Li 2012;Shimizu & Hitt 2004;Yiu et al 2007). These firms use both intangible (knowledge) and tangible (assets) resources to transfer acquired resources to firm-specific advantages (Bierly & Chakrsbarti 1996), thus enhancing their strategic advantage (Dannels 2002).…”
Section: Shimizu and Hitt 2004)mentioning
confidence: 99%
“…Both control and coordination have been identified as two important activities in the management of software projects, in general, (Banker et al 2006;Choudhury and Sabherwal 2003;Kirsch 1997) as well as in offshore software projects, in particular (Sabherwal and Choudhury 2006). Although the two types of costs are interrelated in that "(…) [i]mproved coordination helps in the exercise of control while effective control may improve coordination" (Sabherwal and Choudhury 2006, p. 190), they represent two distinct concepts (Benslimane et al 2005;Sabherwal and Choudhury 2006;White and Lui 2005).…”
Section: Control and Coordination Costsmentioning
confidence: 99%